Safe perioperative management of major hepatectomy in a patient with portal hypertension after elimination of hepatitis C: a case report - Ryoga Hamura; Shinji Onda; Yoshihiro Shirai; Jungo Yasuda; Koichiro Haruki; Kenei Furukawa; Taro Sakamoto; Takeshi Gocho; Toru Ikegami (Surgical Case Reports)
Abstract Background The administration of direct-acting antiviral agents in patients with liver cirrhosis and hepatitis C has been shown to improve liver function and long-term prognosis after sustained virological response (SVR) is achieved. However, in patients with portal hypertension (PH) at the time of SVR, PH may persist despite improvement in liver function. Case presentation An 82-year-old woman with liver cirrhosis due to hepatitis C was treated with direct-acting antiviral agents and achieved SVR. During follow-up, computed tomography revealed a low-density tumor in the left lateral region of the liver with dilation of the left intrahepatic bile duct. Considering the patient’s advanced age and PH persistence with a mild decrease in liver reserve function after SVR, preoperative percutaneous transhepatic portal embolization (PTPE) and partial splenic embolization (PSE) were performed concomitantly. Laparoscopic left hemihepatectomy was performed 8 days after the PTPE and PSE. The patient was discharged 8 days after surgery without any postoperative complications. Conclusions Laparoscopic left hemihepatectomy after preoperative management of PH was performed safely in a patient after the elimination of hepatitis C.